2013
DOI: 10.2106/jbjs.k.00190
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Origin Slide for Contracture of Spastic Finger Flexor Muscles

Abstract: The Page-Scaglietti technique appears to improve range of motion and function in people with wrist and finger contractures due to central nervous system disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Previous publications have shown the long-term benefit of upper limb surgery in severe spasticity, mostly with regards to function, appearance or hygiene (Heijnen et al., 2008; Keenan et al., 1987; Peraut et al., 2018; Pomerance and Keenan, 1996; Thevenin-Lemoine et al., 2013). The patients we treated were in the worst group of the Keenan classification (Keenan et al., 1987) for hand position and would have been rated as 0 (=does not use hand) in the functional classification of House et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have shown the long-term benefit of upper limb surgery in severe spasticity, mostly with regards to function, appearance or hygiene (Heijnen et al., 2008; Keenan et al., 1987; Peraut et al., 2018; Pomerance and Keenan, 1996; Thevenin-Lemoine et al., 2013). The patients we treated were in the worst group of the Keenan classification (Keenan et al., 1987) for hand position and would have been rated as 0 (=does not use hand) in the functional classification of House et al.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures for the non-functional spastic upper limb have been shown to be effective in the longer term (Heijnen et al., 2008; Keenan et al., 1987; Pomerance and Keenan, 1996). Past publications have reviewed improvement in function and hygiene, or measured opening of the fingers (Facca et al., 2010; House et al., 1981; Keenan et al., 1987; Thevenin-Lemoine et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Three patients with an anoxic brain lesion (two stroke patients SP1, SP2, and one CP patient SP3) were recruited through the hand surgeon's clinic. The criteria for eligibility and inclusion in the study were (Thevenin-Lemoine et al, 2013) upper limb spasticity due to an anoxic brain lesion, Photopoulos et al (2014) observed gait abnormalities, Sheean (2002) an ability to ambulate independently with or without assistive devices, and (Emos and Agarwal, 2018) no history of previous surgery to release spasticity in the upper limb. In all three patients, there were no pharmacological treatment to reduce spasticity and no history of rehabilitation on upper or lower limbs within 6 months prior to enrollment in the study.…”
Section: Patientsmentioning
confidence: 99%
“…Impairments of motor and sensory function and coordination are often consequences of injury to the central nervous system (Thevenin-Lemoine et al, 2013;Photopoulos et al, 2014). Upper motor neuron syndrome (UMNS) is a condition that arises as a result of the disturbance of the UMN inhibitory pathways extending all the way from the cerebral cortex to the lower end of the spinal cord (Sheean, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation